The Effectiveness of Osmofilter Paper Wrapped Lime and Alum in Improving the Water Quality of the Siak River Water - Alvie Kharisma; Budijono '; Sampe Harahap (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
Combination of lime and alum can be used to improve thequality of the river water. The lime used, however, is not completely diluted and it forms flocks. To find out the effective dosages of lime (L) and alum (A) and to understand the effectiveness of osmofilter paper (O) in improving water quality of the river water, a study has been conducted on April – June2016. The were 4 treatments applied, namely Po (no L, A and O); P2 (150 mg L + 150 mg A + O); P2 (150 mg L + 350 mg A + O) and P3 (150 mg L + 550 mg A + O). The wrapped lime and alum was then immersed in 10L of river water for 30 minutes. The treated water was then used to rear Cyprinus carpio, 10 fishes/ aquarium for 4 days period. Results shown that P2 was the best, as the TSS reduced, from 21.33 to 0.1 mgL-1, the turbidity reduced from 30.83 to 1/.62 NTU, the color reduced from 265.67 to 13.33 Pt/Co and the survival rate of the fish was 100%. Based on data obtained, it can be concluded that the osmofilter paper wrapped lime and alum is effective in improving the quality of the Siak River water.Keyword : Siak River, osmofilter paper, lime, alum